A short note on honorifics and personal articles in Spanish and Catalan: Consequences for the theory of proper names - Saab, Andrés Leandro (2021)
Building on recent findings in Bernstein et al. (2019), regarding the syntactic distribution of personal articles in Catalan and honorifics in Spanish, I propose that they are pure expressives (in Potts' (2005) sense) that take an entity as argument and return the same entity at the at-issue level and a conventionally implicated proposition in a parallel meaning dimension. If this analysis turns out to be correct, the expressive / proper name interaction in these languages will constitute a new piece of evidence against the predicative analysis of proper names.